Psychological Problems and Challenge In EFL Speaking Classroom - Win Listyaningrum Arifin (UIN Salatiga, 2017)
Psychological aspect regarding to learning attitudes plays in determining learning achievement. Psychological problems also involve not only to the students but also teacher. Less-confidence, speech anxiety, and low self-esteem are almost common problem in classroom, and occur on both teachers and students. Students who have low of self-confidence are often hardly able to control themselves for public speaking in the classroom, like, Governing his/ her behavior on that his/her peers think, lose belief on self, thinking that his/her friends dis-appraising, afraid of getting mistakes, etc. However, teachers which are low self-esteem and confidence also lose their performance and ability to manage their classroom optimally. Low self-esteem may caused by teacher’s poor understanding on subject matter. Both of psychological problems impact on dis-effectiveness of classroom activities. This paper takes accounts of some psychological problems of students and teachers in English speaking classroom, and some guidelines to overcome. At the last discus, this paper also provides some keys of how to make good classroom atmosphere.